LWR1 and LWR2 Are Required for Osmoregulation and Osmotic Adjustment in Arabidopsis - Verslues, Paul E. (American Society of Plant Biologists, 2004)
With the goal of identifying molecular components of the low-water-potential response, we have carried out a two-part selection and screening strategy to identify new Arabidopsis mutants. Using a system of polyethylene glycol-infused agar plates to impose a constant low-water-potential stress, putative mutants impaired in low-water-potential induction of the tomato (Lycopersicon esculentum) le25 promoter were selected. These lines were then screened for altered accumulation of free Pro. The seedlings of 22 mutant lines had either higher or lower Pro content than wild type when exposed to low water potential. Two mutants, designated low-water-potential response1 (lwr1) and lwr2, were characterized in detail. In addition to higher Pro accumulation, lwr1 seedlings had higher total solute content, greater osmotic adjustment at low water potential, altered abscisic acid content, and increased sensitivity to applied abscisic acid with respect to Pro content. lwr1 also had altered growth and morphology. lwr2, in contrast, had lower Pro content and less osmotic adjustment leading to greater water loss at low water potential. Both lwr1 and lwr2 also had altered leaf solute content and water relations in unstressed soil-grown plants. In both mutants, the effects on solute content were too large to be explained by the changes in Pro content alone, indicating that LWR1 and LWR2 affect multiple aspects of cellular osmoregulation.